How English Language Teachers' Expectation Affects Students' English Learning Motivation - Ramadhani, Aulia Citra; Purnawan, Ari (Lingua Pedagogia, 2023)
To master English, students are expected to be eager enough to learn on their own. It is generally assumed that English teachers' expectations of their students affect students' willingness to learn English by themselves. According to their expectation, teachers tend to behave unconsciously differently toward their students (Sarah et al., 2020). These different behaviors could inflict how the students feel about the learning activity which results in students' eagerness to learn about a certain topic. (Ruesch et al, 2012). This study aims to look into how English Teachers' expectation towards their students' ability affects students' motivation to develop their English skills, especially in Indonesia EFL context. This study result in conclusion Indonesian students' varied characteristics may obstruct their teachers' low or high expectation. There is a possibility that teachers' different expectation affects how they behave towards their students. Therefore, teachers' different behaviors toward their students may affect students' motivation during English learning activities in the classroom. To avoid the possibility of this issue, teachers are advised to help students to reach their optimum potentials, be more sensitive toward their students' emotions, and maintain their rapport during